WHO IS AFRAID OF GENDER?: STUDENTS’ RESISTANCE TO CRITICAL LANGUAGE TEACHING IN REACTIONARY TIMES - da Silva, Leonardo (Revista X, 2020)
This article reports on an action-research conducted by a teacher-researcher with a group of 20 high school students taking the English subject in a federal school in Southern Brazil. Based on the principles of both Task-based language teaching and Critical Pedagogy, critical tasks focusing on gender in the world of work were designed and implemented by the teacher-researcher. Data was collected through students’ questionnaires and interviews, and my self-report diaries. The thematic analysis of the data revealed students’ resistance to the theme approached in the critical tasks. The study points out that students’ opposition to critical reflection seems to be connected to the fact that critical classes deviate from their expectations of what teaching is, since critical teaching moves away from the traditional banking education. A critical understanding of students’ contexts (including the macro sociopolitical scenario) is necessary so that rejection may become resistance towards freedom and social justice.